Views about the clinical, diagnostic and comprehensive treatment of plantar fasciitis: a review - Georgii A. Airapetov; Daniil G. Agafonov; Mikhail S. Serdobintsev; Alexander S. Kaftyrev (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2024)
INTRODUCTION. One of the problems in modern podiatry is plantar fasciitis. According to population studies, more than two million patients are treated for plantar fasciitis each year in the United States, 1 in 10 people will develop heel pain during their lifetime, and 1 % of visits to podiatrists are related to heel pain. Plantar fasciitis occurs in approximately 10 % of the general population, with 83 % of these patients being active working adults between the ages of 25 and 65. The high prevalence of plantar fasciitis in the population necessitates the search and development of new and effective methods for its recognition and treatment. AIM. Generalization of literature data on the mechanisms of development of plantar fasciitis, methods of diagnosis and treatment. MATERIALS AND METHODS. The databases PubMed, Scopus and the electronic scientific library eLIBRARY were searched for articles using the keywords: "plantar fasciitis", "plantar fasciosis", "heel pain", "heel spur". Search depth - 10 years. Publications related to the diagnosis and treatment of PF were selected. During the study, 40 publications were selected, the content of which, to one degree or another, corresponded to the purpose of this study. RESULTS AND DISCUSSION. Pain syndrome in the area of the heel bone is the main reason for seeking medical care in patients with plantar fasciitis. Currently, there are several approaches to the treatment of plantar fasciitis: conservative and surgical treatment. Conservative treatment is represented by methods of manual therapy, physical therapy, and physical therapy. Surgical methods include various variants of resection of the bony outgrowth of the calcaneal region and other interventions. CONCLUSION. Treatment of plantar fasciitis requires a multidisciplinary approach to treatment, as no single treatment method is universal. Conservative treatment of patients with plantar fasciitis should be comprehensive. Due to the high prevalence of plantar fasciitis in the population, the introduction of new treatment techniques and the development and use of a unified patient management tactic can improve patient outcomes and quality of life. Among other surgical methods, the use of RFD has a positive effect in patients with PF refractory to conservative therapy and is the least invasive method among surgical methods.